CWC22 Connects Pre-mRNA Splicing and Exon Junction Complex Assembly - Anna-Lena Steckelberg; Volker Boehm; Agnieszka M. Gromadzka; Niels H. Gehring (Cell Reports, 2012)
The exon junction complex (EJC) is a key regulator of posttranscriptional mRNA fate and binds to mRNA during splicing. Although the composition of EJCs is well understood, the mechanism mediating splicing-dependent EJC assembly and the factor(s) recruiting the EJC remain elusive. Here, we identify CWC22 as an essential splicing factor that is required for EJC assembly. In CWC22-depleted cells, pre-mRNA splicing is impaired but is rescued by a central fragment of CWC22. We show that the MIF4G domain of CWC22 initiates EJC assembly via a direct interaction with the EJC core protein eIF4A3, and we characterize mutations in eIF4A3 that abolish binding to CWC22. These eIF4A3 mutants efficiently nucleate splicing-independent recombinant EJC core complexes, but they fail to support splicing-dependent EJC deposition. Our work establishes a direct link between the splicing machinery and the EJC, hence uncovering a molecular interaction at the center of a posttranscriptional gene regulation network.